2020
DOI: 10.52943/jikeperawatan.v6i1.339
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Keluarga Dengan Kepatuhan Diet Pada Pasien Gagal Ginjal Kronik Di Rumah Sakitumum Imelda Pekerja Indonesia (Rsu Ipi) Medan Tahun 2019

Abstract: ABSTRAK   Gagal ginjal kronik ( chorinic renal failure ) adalah kerusakan ginjal prosesif yang berakibat fatal yang di tandai dengan uremia (urea dan limbah nitrogen lainnya yang beredar dalam darah serta komplikasinya jika tidak dilakukan dialisis atau transpalasi ginjal ). Dukungan yang di berikan keluarga terhadap pasien yang menjalankan terapi diet sehingga pasien merasaka nyaman. Jenis penelitian menggunakan penelitian kuantitatif dengan tujuan penelitian untuk mengetahui hubungan dukungan kel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Knowledge of maintaining oral hygiene alone is not enough without action in cleaning teeth, both must work in balance. There are various outcomes when a person did not taking care of their oral hygiene such as caries, periodontal disease, plaque, halitosis, gingivitis, and others more (Manurung, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of maintaining oral hygiene alone is not enough without action in cleaning teeth, both must work in balance. There are various outcomes when a person did not taking care of their oral hygiene such as caries, periodontal disease, plaque, halitosis, gingivitis, and others more (Manurung, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After the increase in blood pressure lasts for a long time, there is damage to small blood vessels and increased resistance of flow and reduction of blood flow in the eye accompanied by loss of ganglion cells which will result in flow retention and fluid buildup resulting in an increase in intraoculi pressure (Fraser et al, 2012). Based on research conducted (Manurung et al, 2023) at DR. Soetomo General Hospital Surabaya, found that patients who have suffered from hypertension ≥ 5 years are at risk of developing glaucoma by four times greater.…”
Section: Introductionmentioning
confidence: 99%